The Effect Of Question And Answer Relationship (QAR) Strategy On Grade XI Vocational Students' Reading Comprehension: An Explanatory Mixed-Methods Study - Ilmuislami Mawardin; Mawardin Muhammad Said; Mukrim Mukrim; Jamiluddin Jamiluddin; Darmawan Darmawan (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aims to examine the effect of the Question–Answer Relationship (QAR) strategy on the reading comprehension of Grade XI vocational high school students and to explore students’ perceptions of its implementation in EFL reading instruction. This research employed an explanatory sequential mixed-methods design involving 51 students from a vocational high school in Indonesia, divided into an experimental class (n = 27) and a control class (n = 24). Quantitative data were collected through pretest and posttest reading comprehension tests and analyzed using an independent samples t-test. The results revealed that students taught using the QAR strategy achieved significantly higher posttest scores (M = 83.85) than those taught through conventional instruction (M = 67.29). Qualitative data obtained from classroom observations, questionnaires, and semi-structured interviews indicated increased motivation, confidence, critical thinking skills, and strategic awareness in reading. Despite initial difficulties in categorizing question types, students responded positively to the strategy after consistent practice. The integration of quantitative and qualitative findings demonstrates that the QAR strategy not only improves students’ reading comprehension outcomes but also fosters positive learning behaviors. Therefore, the QAR strategy is an effective instructional approach for improving reading comprehension in vocational EFL classrooms.